Approach to physiotherapy in sexual dysfunctions: Literature review (International Seven Journal of Multidisciplinary, 2023)
This integrative review study aimed to describe the role of physiotherapy in improving sexual dysfunction and increasing libido. The data search was carried out in the databases PubMed, Latin American and Caribbean Literature in Health Sciences (LILACS), SciELO and Google Scholar with the descriptors: sexual dysfunction, libido, menopause, role of physiotherapy in increasing libido. The screening of the articles found was carried out by reading the title, reading the summary, and, even in case of doubt, the article was read in full and selected according to the inclusion and exclusion criteria. After filtering and analyzing the publications, a selection process was carried out involving 11 articles, 5 of which were used to compose the table. It was evident in this review that there are different contexts experienced in the work of physiotherapists. The physiotherapist works to improve the flexibility of the pelvic floor muscles, leading to the relief of pelvic and/or abdominal pain. Various therapies are used, including: Kinesiotherapy, Electrostimulation, In this scenario, the studies used and the reviewers of this research point to the need for continued research on the subject to strengthen evidence-based practice.